A Rare Case of Pulmonary Lymphangitic Carcinomatosis in a Young Adult with Carcinoma Stomach - Prasanta Kumar Bhattacharya; Md. Jamil; Yookarin Khonglah; Aakash Roy; Murti V. Subrahmanya (Journal of Clinical and Diagnostic Research, 2017)
Pulmonary Lymphangitic Carcinomatosis (PLC) occurs in about 6-8% of patients with lung metastasis and may rarely develop in the course of gastric cancer representing a complication due to diffuse metastasis in the lymphatics of the lungs. A 29-yearold female, admitted with difficulty in breathing and productive cough for one week, was initially evaluated for respiratory tract infection. During evaluation of associated anaemia an upper gastrointestinal endoscopy showed large ulcerative growth in the lesser curvature of the stomach suggestive of carcinoma. A High Resolution Computed Tomographic (HRCT) scan of the lungs was done for evaluation of the pulmonary opacities on chest x-ray which showed nodular thickening of interlobular septa with peribronchial cuffing and fissural thickening. The biopsy of the gastric ulcer was suggestive of poorly differentiated malignancy. With the cumulative results of the investigations a diagnosis of poorly differentiated carcinoma of stomach with pulmonary metastasis as lymphangitic carcinomatosis was made. PLC is an extremely rare manifestation of metastatic gastric cancer. Though associated with an extremely poor prognosis, advanced gastric cancer in younger patients presenting with symptoms and signs of respiratory disease should alert the physician of a possible diagnosis of PLC.